Identification of Rotavirus VP6-Specific CD4+ T Cell Epitopes in a G1P[8] Human Rotavirus-Infected Rhesus Macaque - Zhao, Wei (2008)
A non-human primate model was used to evaluate its potential for identification of rotavirus viral protein 6 (VP6) CD4+ T cell epitopes. Four juvenile rhesus macaques were inoculated with a mixed inoculum (G1P[8] and G9P[8]) of human rotaviruses. Infection accompanied by G1P[8] shedding was achieved in the two macaques that had no rotavirus immunoglobulin A (IgA) in plasma. To measure the interferon gamma (IFN-γ) and tumor necrosis factor (TNF) anti-viral cytokines produced by peripheral CD4+ cells that recognize VP6 epitopes, whole blood cells from one infected macaque were stimulated in vitro with VP6 peptides. Stimulation with peptide pools derived from the simian rotavirus VP6(161–395) region revealed reactivity of CD4+ T cells with the VP6(281–331) domain. A VP6(301–315) region was identified as the epitope responsible for IFN-γ production while a broader VP6(293–327) domain was linked to TNF production. These results suggest that human rotavirus-infected macaques can be used for identification of additional epitopes and domains to address specific questions related to the development of pediatric vaccines.